2016
DOI: 10.1186/s12906-016-1394-4
|View full text |Cite
|
Sign up to set email alerts
|

Douchi (fermented Glycine max Merr.) alleviates atopic dermatitis-like skin lesions in NC/Nga mice by regulation of PKC and IL-4

Abstract: BackgroundDouchi (fermented Glycine max Merr.) is produced from fermented soybeans, which is widely used in traditional herbal medicine. In this study, we investigated whether Douchi attenuates protein kinase C (PKC) and interleukin (IL)-4 response and cutaneous inflammation in Atopic dermatitis (AD)-like NC/Nga mice.MethodsTo induce AD-like skin lesions, D. farinae antigen was applied to the dorsal skin of 3-week-old NC/Nga mice. After inducing AD, Douchi extract was administered 20 mg/kg daily for 3 weeks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 67 publications
5
14
0
2
Order By: Relevance
“…In Korean medicine, Hataedock (HTD), herbal extracts that are orally administered to neonates and infants, was used to clear fetal heat to prevent inflammatory diseases. Our previous studies have shown that HTD mitigates AD development due to fetal heat and controls 2skewed conditions [26,27]. Moreover, our studies showed that lipid barrier formation in the epidermis is increased after the application of HTD [28].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…In Korean medicine, Hataedock (HTD), herbal extracts that are orally administered to neonates and infants, was used to clear fetal heat to prevent inflammatory diseases. Our previous studies have shown that HTD mitigates AD development due to fetal heat and controls 2skewed conditions [26,27]. Moreover, our studies showed that lipid barrier formation in the epidermis is increased after the application of HTD [28].…”
Section: Introductionsupporting
confidence: 54%
“…In particular, genistein, a modest fatty acid amide hydrolase (FAAH) inhibitor, can prevent proinflammatory response in a CB1/ CB2-dependent manner [33]. In our previous study, we found that Douchi extract contains more genistein than raw soybeans [26].…”
Section: Introductionmentioning
confidence: 97%
“…N-Nitroso compounds are derived from biogenic amines that are ubiquitous in high-protein fermented foods such as douchi [16,17]. It has also been used as a medicine for high blood pressure [18] and inflammatory disease (i.e., 'heat' syndrome in Chinese medicine) [19]. Among different biogenic amines, histamine and tyramine are considered to be the most toxic and are of public health concern [20-22].…”
Section: Introductionmentioning
confidence: 99%
“…5) , 한약재를 달인 약물을 부드러운 천이나 비단에 묻혀 입안을 닦아주면서 소량 먹이는 방법이다 6) . 두시법 (豆 豉法), 감초법 (甘草法), 황련법 (黃連法), 주밀법 (朱蜜 法) 등이 있으며, 이 중 두시는 해표 (解表)시키는 효능 이 있어 염증 증상들을 완화시킨다 [7][8][9] . 선행연구에 의 하면 발효 콩이 AD 증상 완화와 소양감 억제 효과가 있음을 보고하고 있으며 10) , Th2 response를 통한 Th1과…”
unclassified